Biochemical and histological features of somatic embryogenesis in Hevea brasiliensis - Carron M P; DAuzac J; El Hadrami I; Etienne H; Housti F; Montoro P; sMichaux-Ferriere N (Indian Journal of Natural Rubber Research, 1992)
Basic studies were carried out to improve somatic embryogenesis in Hevea. These investigations called for histological and biochemical analyses of plant material and culture media in relation to water, atmospheric gases in culture vessels, minerals, polyamines, phenols and growth regulators. Mechanisms of womatic embryogenesis are partially outlined with the help of histologoical and biochemical evidences at each step of culture. In primary culture, water parameters and mineral analyses indicated that initiation of exchanges between medium and explant has to be enhanced. During callus development metabolism of ethylene and polyamines is very active and must be controlled by adjustment of growth regulators by the type of medium support and/or by inhibitor supply. Disorganisation of the oxidative metabolism has been studied in relation to browning of the callus. Adjustment of culture medium to enhance somatic embryogenesis has been correlated with the setting up of a specific water status in the embryogenic callus. Embryogenesis can be expressed in two different forms depending on cultural conditions and genotype. Enhancement of the basic knowledge led to systematic embryogenesis from the clones PB 260, PB 235, PR 107 and RRIM 600.
Keywords: France; Growth regulators; Hevea brasiliensis; Histology; Somatic embryogenesis